Cassava Diseases Evaluation - Edaphoclimatic Zone 3: Lowland Tropics; Short or Absent Drought, High Precipitation - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2019)
CIAT systematically evaluates all germplasm accessions in diverse sites in Colombia, to obtain a broad characterization of adaptation to different soils and climates, resistance to many pests and diseases, and quality traits. The information is used primarily to select parents which can potentially contribute characters requested by national programs. Based on these evaluations, some generalized conclusions can be drawn regarding the genetic potential of cassava landrace varieties.